Fuel subsidies and carbon emission: Evidence from asymmetric modelling - Ibrahim A. Adekunle; Isiaq Olasunkanmi Oseni (African Governance and Development Institute (AGDI), 2021)
It is expected that fuel subsidy removal should hinder carbon emissions growth through low energy consumption channels amid higher energy prices. However, outliers in this theoretical disposition make empirical proof of the fuel subsidy-carbon intensity apt and primitive. Despite established fuel subsidy abolishment gains for climate and economic welfare, the relevance, magnitude and policy implications remain dimly. This paper employs the non-linear autoregressive distributed lag (NARDL) estimation procedure to gauge the contemporaneous influence of fuel subsidy for carbon intensity in Nigeria. Findings revealed that fuel subsidy removal inversely relates to Nigeria's carbon emission in the short-run and long run. The study recommends complementary policy option that ensures additional financial savings to the government should be invested in public sector growth that can cushion the effect of relative income loss to the citizenry. The Nigerian government should ensure measures are kept in place to discourage over-consumption of alternative energy (for example, coal) that could also threaten the green economy paradox.
Keywords: C22; E31; N57; Q54; 330; Fuel Subsidy; Carbon Emission; Non-linear ARDL; Nigeria